2009
DOI: 10.1021/ac901890r
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent-Dye-Doped Sol−Gel Sensor for Highly Sensitive Carbon Dioxide Gas Detection below Atmospheric Concentrations

Abstract: Optical fluorescence sol-gel sensors have been developed for the detection of carbon dioxide gas in the 0.03-30% range with a detection limit of 0.008% (or 80 ppm) and a quantitation limit of 0.02% (or 200 ppm) CO(2). Sol-gels were spin-coated on glass slides to create an organically modified silica-doped matrix with the 1-hydroxypyrene-3,6,8-trisulfonate (HPTS) fluorescent indicator. The luminescence intensity of the HPTS indicator (513 nm) is quenched by CO(2), which protonates the anionic form of HPTS. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…The optical sensors have also been designed to function in a multianalyte platform for the simultaneous detection of multiple gas analytes. The studies here follow our earlier work in the development of optical sensors for chemicals in both liquid and gas phases [35]- [39].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The optical sensors have also been designed to function in a multianalyte platform for the simultaneous detection of multiple gas analytes. The studies here follow our earlier work in the development of optical sensors for chemicals in both liquid and gas phases [35]- [39].…”
Section: Introductionmentioning
confidence: 85%
“…The optimum particle size would be approximately 0.5 times the wavelength of interest which, in this case, would be around 250 -350 nm for the emission wavelength of 550 nm from the dye. This method was adapted from CO 2 sensors that we developed recently [39]. One possible method using TiO 2 particles would be to prepare size-controlled TiO 2 particles so that it would correspond to the optimum particle size needed for the emission wavelength.…”
Section: Mie Scattering With Tio2 Particlesmentioning
confidence: 99%
“…For instance, Sampathkumaran et al reported the development of a sol-gel fluorescent sensor for detecting CO 2 with a detection limit below the amount of CO 2 in the atmosphere (ca. 387 ppm) (Figure 11b) [43]. In their work, a sol-gel fluorescent sensor was modified into silica-doped matrix with 11 by spin coating on glass slides.…”
Section: Carbon Dioxide (Co 2 ) Detectionmentioning
confidence: 99%
“…Another class of gas sensor exploits optical properties. The optical gas sensors are used in fire and explosion prevention, healthcare, indoor air quality control, leak detection, food production and process optimization and control, among the other applications [13]. This particulate technology has progressed rapidly and now-a-days the optical gas sensors are capable to monitor multiple gases, sometimes remotely at a distance of a kilometer or more.…”
Section: Introductionmentioning
confidence: 99%